2(3a+1)=5(a-1)

Simple and best practice solution for 2(3a+1)=5(a-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3a+1)=5(a-1) equation:


Simplifying
2(3a + 1) = 5(a + -1)

Reorder the terms:
2(1 + 3a) = 5(a + -1)
(1 * 2 + 3a * 2) = 5(a + -1)
(2 + 6a) = 5(a + -1)

Reorder the terms:
2 + 6a = 5(-1 + a)
2 + 6a = (-1 * 5 + a * 5)
2 + 6a = (-5 + 5a)

Solving
2 + 6a = -5 + 5a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-5a' to each side of the equation.
2 + 6a + -5a = -5 + 5a + -5a

Combine like terms: 6a + -5a = 1a
2 + 1a = -5 + 5a + -5a

Combine like terms: 5a + -5a = 0
2 + 1a = -5 + 0
2 + 1a = -5

Add '-2' to each side of the equation.
2 + -2 + 1a = -5 + -2

Combine like terms: 2 + -2 = 0
0 + 1a = -5 + -2
1a = -5 + -2

Combine like terms: -5 + -2 = -7
1a = -7

Divide each side by '1'.
a = -7

Simplifying
a = -7

See similar equations:

| 66-2r+1=3r-5(r-2) | | F(10.5)= | | 28+x=14 | | 6=x-3/2 | | 2(p+5)-3(p-7)=43 | | (9x^7)(-8x^5)=0 | | 10(d+9)=210 | | 7x-7-5x=2 | | 40-[3c+4]=4[c+5]+c | | 40-[3c+4]=[c+5]+c | | 4m-3=6m+5 | | -7t+4=-10t-14 | | 4[m+4]=40 | | -7+4=-10+-14 | | 2x+50=110 | | 14x^4+92x-42x^2=0 | | 2x-3y+i(x-2y)=4-5i | | -4(7-5m+n)= | | 6+4b=2+5b | | -3=21m | | M+2M-2=0 | | 6(w+1)-(3-2w)=7w | | 3x2squared/12x6squared | | 9m+13=58 | | 3z+8-z=9+z-5 | | 6P+8Q-4=0 | | 304=8p+4(6+8p) | | n+5+2n+3n=41 | | 10-(x+8)=8x-7 | | 2p-6p=5 | | P-2.6=58.4 | | 6y^2+31y+35=0 |

Equations solver categories